The role of innovative technology to improve patient centered care - Nabilla, Fira; Krongthaeo, Suphanna; Dianingati, Ragil Setia; Annisaa', Eva (Universitas Muhammadiyah Magelang, 2021)
Chronic disease is a long term disease. Treatment performed by patients is also routine and continuous to achieve therapeutic success as well as to avoid complications that can be occurred. Adherence is an important factor to reduce complications of chronic disease. There are some efforts that need to do to increase compliance, such as providing information about drug usage from health providers. The use of technology can also be an option as a facility to increase compliance, such as using audiovisual media as an additional means of providing information and short message services or a mobile application for medication reminders on smartphones. This article provides an overview of the role of technology in increasing adherence to patients especially those who are suffering from chronic disease. This article is based on a literature study from some literature or research results. The reviewed literature shows that the use of video in providing information about drugs, sending short messages, and the use of mobile medication reminders to take medication has an effect on increasing adherence significantly in chronic disease patients. The use of technology is effective and efficient in increasing adherence of chronic disease patients.